Skull based osteomyelitis due to postsurgery malignant otitis externa presenting as stroke. (24th May 2011) - Su, Nicola; Syed, Irfan; Garth, Richard
Abstract : Malignant or necrotising otitis externa is a rare but potentially fatal disease. The classic presentation is one of severe, unremitting, throbbing otalgia, which may progress to osteomyelitis, especially in the elderly diabetic or immunocompromised patient. The case described is of a 72-year-old immunocompetent, non-diabetic man who presented with facial weakness, dysphagia and weight loss. The admitting diagnosis or impression was that of a cerebrovascular event. The eventual diagnosis was that of skull based osteomyelitis secondary to malignant otitis externa complicating mastoid surgery.